Polymers for quorum sense interference - Xue, Xuan (2013)
The synthetic polymers reported in this thesis are able to bind the small molecule autoinducer-2 (AI-2) in the Quorum Sense (QS) pathways of the marine organism with high affinity, and some of the polymers are also able to sequester rapidly the same bacteria from suspension. Specifically, the Alizarin Red S (AR-S) assay was used to compare binding interactions of boric and boronic acid with diol species, and interactions were further probed by 11B-NMR spectroscopy and Mass spectrometry. Dopamine was considered as a potential AI-2 scavenger for polymeric QS control owing to the high binding affinities for boron. Therefore, poly{N-(3,4-dihydroxyphenethyl) methacrylamide-co-N-[3-(dimethylamino)propyl] methacrylamide} [p(DMAm-c-DMAPMAm)] and poly(3,4-dihydroxy-L-phenylalanine methacrylamide) [p(L-DMAm)] were prepared via Reversible Addition Fragmentation Chain Transfer (RAFT) polymerization and characterized by 1H-NMR spectroscopy. The activities of these catechol polymers and carbohydrate-based poly(β-D-glucosyloxyethyl methacrylate) (p(GlcEMA)) in QS interference was demonstrated by bioluminescence assays with the Vibrio harveyi MM32 strain and by bacterial aggregation experiments. Polymersomes were then investigated as artificial protocells, with a view to establishing polymer vesicle containers as both reservoirs of QS mediated molecules, and of binding QS agents and bacteria. Hydrophobic monomers N-(2-Ethylhexyl) acrylamide [p(2-EHAm)] and N-phenylacrylamide [p(PAm)] were therefore polymerized into block copolymers from p(L-DMAm)-RAFT agents. The membrane permeability of polymersomes was measured via encapsulation and release of dyes, while the morphologies were examined with Dynamic Light Scattering (DLS) and Transmission Electron Microscopy (TEM). Polymersomes were also investigated for potency in QS quenching via the bioluminescence assay and bacterial aggregation experiments. Initial studies of a communication feedback loop between bacteria and polymersome-encapsulated QS agents were performed again via bioluminescence assays. The results reveal that the investigated polymersomes exhibit potent activities in QS quenching, and further development might act as components of a synthetic biology approach to combating microbial pathogenicity.